2011
DOI: 10.1021/ed100079t
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Journal Inquiry Laboratory: A Case Study in a General Chemistry Kinetics Experiment

Abstract: The mini-journal curriculum for undergraduate science laboratories mirrors the format of scientific literature and helps students improve their learning through direct scientific practices. The lab embodies the essential features of scientific inquiry and replaces the traditional “cookbook” lab to engage students in active learning. A case study of a mini-journal lab in college general chemistry, including its design, instruction, and reflections, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…We based this design component upon research that showed that paraprofessional contexts frequently yield a higher level of student engagement than is normally generated through the use of more traditional assignment structures such as essays or stand-alone, abstract writing modules (Antonius, Brown, Todman & Safran, 2007;Gresty & Edwards-Jones, 2012). Similarly, interactive writing projects tend to encourage students to become more invested in the content and therefore assist in developing their own research interests (Antonius et al, 2007;Zhao & Wardeska, 2011). The incorporation of these elements into the pedagogical structure is also in keeping with best practices in online tutorial design (Blummer & Kritskaya, 2009;Erhel & Jamet, 2013;All et al, 2016;Hamari et al, 2016).…”
Section: Designing the Online Experiencementioning
confidence: 99%
“…We based this design component upon research that showed that paraprofessional contexts frequently yield a higher level of student engagement than is normally generated through the use of more traditional assignment structures such as essays or stand-alone, abstract writing modules (Antonius, Brown, Todman & Safran, 2007;Gresty & Edwards-Jones, 2012). Similarly, interactive writing projects tend to encourage students to become more invested in the content and therefore assist in developing their own research interests (Antonius et al, 2007;Zhao & Wardeska, 2011). The incorporation of these elements into the pedagogical structure is also in keeping with best practices in online tutorial design (Blummer & Kritskaya, 2009;Erhel & Jamet, 2013;All et al, 2016;Hamari et al, 2016).…”
Section: Designing the Online Experiencementioning
confidence: 99%
“…The most important dimension of the nature of science is the way of reaching information and the phases of the scientific method. Inquiry can be considered as a strategy to develop various skills and help students to gain new information (Aljaafreh, 2013;Opateye, 2012;Zhao & Wardeska, 2011). Inquiry can also assist students in developing the skills needed throughout their lives (Duran & Dokme, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Higher-level process and problem solving skills needed by chemistry and biochemistry graduates have previously been described, and laboratory experience is believed to play an important role in developing these skills; however, traditional expository laboratory design has not been shown to purposefully develop these skills. Inquiry-based design is an alternative approach to traditional “cookbook” style laboratories, and varying levels of inquiry in the undergraduate laboratory have been defined with higher levels of inquiry such as guided-inquiry and open-inquiry sometimes referred to as discovery learning . Process-oriented guided-inquiry learning (POGIL) is a form of student-centered inquiry-based pedagogy that was developed in chemical education. Laboratory activities and experiments based on POGIL have been incorporated into all levels and areas of chemical education, and POGIL has branched out to be incorporated into a number of other educational fields including biomechanics, pharmacy, foreign languages, computer science, and financial literacy . Additionally, inquiry has been utilized in other aspects of the laboratory curriculum to improve information literacy, report writing, and notebook keeping skills. As opposed to the lower-level cognitive processes of knowledge, comprehension, and application which are reinforced in the traditional expository laboratory, inquiry-based laboratory methods are proposed to model the higher-level cognitive processes of analysis, synthesis, and evaluation .…”
mentioning
confidence: 99%